ABDULLA AVLONIY’S PLACE IN HISTORY AND HIS SCIENTIFIC LEGACY - Mirhakimova Feruza Xoldorjon qizi; Vakhobova Gulnoza Avazbek kizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This article examines Abdulla Avloniy, a leading figure of the Uzbek enlightenment movement and one of the most active and influential representatives of the national awakening period, who left a profound mark on the socio-cultural life of Turkestan. His works, such as Birinchi Muallim (The First Teacher), Ikkinchi Muallim (The Second Teacher), and Turkiy Guliston yoxud Axloq (Turkic Garden or Ethics), became key sources in the formation of Uzbek pedagogical thought. Avloniy contributed to the intellectual and moral development of the nation by modernizing the education system, establishing new-method schools, and creating contemporary curricula. His journalistic activity, contributions to the art of theater, and promotion of patriotism and enlightenment played an important role in raising public awareness.